Perceiving the Consumerâ€™s Desire and Transforming it into a Business Model : A Case Study of Morning Fresh, Indiaâ€™s No. 1 Hangover Cure & Detox Drink - Jain, Akshat (Indian Journal of Marketing, 2022)
An increasing number of Indians are drinking alcohol, but the latest study (â€œAlcohol Consumption in India,â€ 2022) shows that the country is experiencing a rise in smart drinking, limiting consumption within limits, and only on social occasions. The study conducted across three North Indian states found that there is now an increase in the number of people who drink at casual get-togethers, festivals, or social occasions; 54% of the respondents said that they drank at such events, while 44% admitted to responsibly following rules and regulations regarding alcohol consumption. According to recent research, the burden of alcohol in India costs the economy more than the Indian governmentâ€™s whole health budget (Jyani et al., 2019). According to the findings of a study that was just recently published in the International Journal of Drug Policy, the economic loss that can be attributed to the negative effects of alcohol consumption accounts for approximately 1.45 percentage points of the total gross domestic product when tax receipts from the sale of alcohol are taken into account (GDP). To put this into perspective, the yearly expenditures of the government on health amount to around 1.1% of the GDP. According to the researchersâ€™ projections, the whole social and economic cost of alcohol-related health disorders in 2050 would be more than the entire gross domestic product of India in 2018, which was INR 219.5 trillion. This development places one company at an advantage in further promoting responsible drinking among liquor drinkers. Looking at such a number of consumers with the social and health impact, the owner of Healthline Private Limited foresaw an opportunity not only to start an exponential revenue-generating product, but also to ameliorate the health problems in youngsters, thereby also limiting their habitsâ€™ ill effects on the society. The CEO of the company had a background of the F&B sector and was skilled in creative leadership, product innovation, and business development. This case examined how Healthlineâ€™s owners transformed an opportunity into a successful business model by introducing the most innovative and acceptable product, â€œMorning Fresh,â€ and underlined how crucial it is to understand customer desires. The case also emphasized the marketing strategies employed to capture the maximum possible market cap. I took the data from secondary sources and published resources (from 2014 to 2021) to analyze the complete case from different perspectives. I also explored how a consumerâ€™s immediate needs and desires can be transformed into a successful business.